Ammonia clearance with haemofiltration in adults with liver disease. Issue 1 (20th June 2013) - Slack, Andrew J.; Auzinger, Georg; Willars, Chris; Dew, Tracy; Musto, Rebecca; Corsilli, Daniel; Sherwood, Roy; Wendon, Julia A.; Bernal, William
Abstract Background & Aims Ammonia is recognized as a toxin central to complications of liver failure. Hyperammonaemia has important clinical consequences, but optimal means to reduce circulating levels are uncertain. In patients with liver disease, continuous renal replacement therapy (CRRT) with haemofiltration (HF) is often required to treat concurrent kidney injury, but its effects upon ammonia levels are poorly characterized. To evaluate the effect of HF at different treatment intensities on ammonia clearance (AC) and arterial ammonia concentration. Methods Prospective study of adult patients with liver failure and arterial ammonia >100 μmol/L requiring CRRT using veno‐venous HF. Arterial ammonia concentration and AC measured at 1 and 24 h after initiation of low (35 ml/kg/h) or high (90 ml/kg/h) filtration volume. Results Twenty‐four patients (10 acute liver failure, 10 chronic liver disease and 4 following liver resection) were studied. Clearance of urea and ammonia solutes correlated closely (r = 0.819, P = 0.007). Ammonia clearance correlated closely with ultrafiltration rate (r = 0.86, P < 0.001). At 1 h, AC was 39 (34–54) ml/min (low volume) vs 85 (62–105) ml/min (high volume) CRRT, (P < 0.001) and at 24 h 44 (34–63) vs 105 (82–109) ml/min, (P = 0.01). Overall, a 22% reduction in median arterial ammonia concentration was observed over 24 h of HF from 156 (137–176) to 122 (85–133) μmol/L, (P ≤ 0.0001). Conclusion Clinically significant ammonia clearance can be achieved in adult patients with hyperammonaemia utilizing continuous VVHF. Ammonia clearance is closely correlated with ultrafiltration rate. HF was associated with a fall in arterial ammonia concentration.